Sex-Differences in Alpha-1 Antitrypsin Deficiency: Data From the EARCO Registry - Ersöz, Hilal; Torres-Durán, María; Turner, Alice M; Tanash, Hanan; Rodríguez García, Carlota; Corsico, Angelo Guido; López-Campos, José Luis; Miravitlles, Marc; Clarenbach, Christian F; Chapman, Kenneth R; Hernández Pérez, José M; Guimarães, Catarina; et al. (Archivos de bronconeumologia, 2025)
BACKGROUND: Sex and gender influence many aspects of chronic obstructive pulmonary disease (COPD). Limited data are available on this topic in alpha-1 antitrypsin deficiency (AATD). We therefore aimed to investigate sex issues in the EARCO registry, a prospective, international, observational cohort study. METHODS: Baseline data from PiZZ individuals, enrolled in the registry with complete data on sex and smoking history were analysed by group comparisons and binary logistic regression analyses. RESULTS: 1283 patients with AATD, 49.3% women were analysed. Females reported less tobacco consumption (16.8±12.2 vs. 19.6±14.5 PY, p=0.006), occupational exposures towards gases, dusts or asbestos (p<0.005 each) and consumed less alcohol (5.5±7.6 vs. 8.4±10.3u/week, p<0.001). Females reported COPD (41% vs. 57%, p<0.001) and liver disease (11% vs. 20%, p<0.001) less often. However, they had a higher prevalence of bronchiectasis (24% vs. 13%, p<0.001). Despite better lung function (FEV1%pred. 73.6±29.9 vs. 62.7±29.5, p<0.001) females reported a similar symptom burden (CAT 13.4±9.5 vs. 12.5±8.9, p=ns) and exacerbation frequency (at least one in the previous year 30% vs. 26%, p=ns) compared to males. In multivariate analyses, female sex was an independent risk factor for exacerbations in the previous year OR 1.6 p=0.001 in addition to smoking history, COPD, asthma and bronchiectasis and was also identified as risk factors for symptom burden (CAT≥10) OR 1.4 p=0.014 besides age, BMI, COPD and smoking history. CONCLUSION: Men had higher rates of COPD and liver disease, women were more likely to have bronchiectasis. Women's higher symptom burden and exacerbation frequency suggest they may need tailored treatment approaches.
Keywords: kouření; alpha 1-Antitrypsin Deficiency; Bronchiectasis; Alpha1-antitrypsin; ženské pohlaví; Smoking; lidé; Pulmonary Disease, Chronic Obstructive; prospektivní studie; Comorbidity; Occupational Exposure; Gender; senioři; sexuální faktory; komorbidita; Aged; Alpha1-antitrypsin deficiency; prevalence; lidé středního věku; pití alkoholu; Prevalence; Chronic obstructive pulmonary disease; Humans; nemoci jater; Alcohol Drinking; chronická obstrukční plicní nemoc; deficit alfa1-antitrypsinu; Prospective Studies; registrace; mužské pohlaví; Male; bronchiektazie; Liver Diseases; Registries; Middle Aged; Sex Factors; Female; pracovní expozice